Analisis Kandungan Protein pada Susu Sapi Perah Kemasan dari Peternakan Desa Gunung Perak Sinjai Barat - Islawati, Islawati; Nurlaela, Nurlaela; Adam, Adam (Yayasan Pendidikan dan Pengembangan Harapan Ananda, 2024)
Humans require food and beverages that serve as building materials, regulators, and sources of energy. Protein is an essential component that functions in tissue maintenance, formation of essential body compounds, antibody production, and maintaining bodily balance. However, the protein content in packaged dairy cow milk can decrease over storage time after packaging, which may affect the nutritional value received by consumers. This study aims to identify and analyze changes in protein levels in packaged dairy cow milk over three days after packaging. The research method used is UV-VIS spectrophotometry with a Genesys 10-S spectrophotometer to measure the protein content in dairy cow milk samples taken from Gunung Perak Village, Sinjai Barat Subdistrict, Sinjai Regency. The results showed that the protein content of the milk one day after packaging was 0.027%, two days after packaging was 0.021%, and three days after packaging was 0.019%. This decrease in protein levels indicates that the duration of storage after packaging negatively affects the protein quality of the milk. The implication of these research findings is the need for special attention in the storage and distribution process of packaged dairy cow milk to maintain its protein content, ensuring that the nutritional value received by consumers remains optimal. Further research with different methods is recommended to obtain more in-depth information about the factors influencing changes in protein levels in the milk.